Genetic Diversity and Population Structure of Brachiaria Species and Breeding Populations. Issue 5 (13th July 2017) - Triviño, Narda Jimena; Perez, Juan Guillermo; Recio, Maria Eugenia; Ebina, Masumi; Yamanaka, Naoki; Tsuruta, Shin‐ichi; Ishitani, Manabu; Worthington, Margaret
Abstract : Several apomictic Brachiaria (Trin.) Griseb. (syn. Urochloa P. Beauv.) species are commercially important tropical forage grasses, but little is known about the interspecific diversity and population structure within this genus. Previously published genus‐level Brachiaria phylogenies were conducted with few genotypes and contradicted well‐established morphological evidence and proven interspecific fertility in the B. brizantha (Hochst. ex A. Rich.) Stapf., B. decumbens Stapf., and B. ruziziensis (R. Germ. & C.M. Evrard) agamic complex. In this study, we characterized the genetic diversity and population structure of 261 genotypes from 14 Brachiaria species and a Panicum maximum Jacq. outgroup using 39 simple sequence repeat primers with 701 polymorphic bands. The genotypes included in the panel included germplasm accessions, commercial cultivars, and sexually reproducing breeding populations. Results of STRUCTURE, neighbor joining, unweighted pair group method with arithmetic mean, and multiple correspondence analyses confirmed the relatedness of the important commercial species B. brizantha, B. decumbens, and B. ruziziensis . Brachiaria decumbens was most closely related to B. ruziziensis, and the diploid sexual and tetraploid apomict B. decumbens accessions formed into two related but distinct groups. The close relationship between B. humidicola (Rendle) Schweick and B. dictyoneura (Figari. and De Not) Stapf. and the unique genetic makeup of the lone sexually reproducing B. humidicola accession were also corroborated by these results. Our findings largely supported morphology‐based taxonomic groupings in Brachiaria and indicated that genus‐level phylogenies are made more robust by the inclusion of many polymorphic markers and multiple genotypes from each species.